Phylogenetic analysis and taxonomic position of section Verrucosa of Panicum and its relationship with taxa of the Sacciolepis–Trichanthecium clade (Poaceae: Panicoideae: Paniceae) - Nicola, Marcela Viviana (2015)
The new genus Kellochloa is proposed, on the basis of morphological and molecular characters, to include two North American species of Panicum s.l., previously classified in sect. Verrucosa: P.brachyanthum and P. verrucosum. Both species are annual, with decumbent culms branching divaricately at the lower nodes, and erect culms with terminal and axillary inflorescences. The spikelets are pilose, with lower glume 1/6 to 1/4 the length of the spikelet, upper glume and lower lemma subequal, 3–5-nerved, the lower anthecium reduced to the lower lemma, and upper anthecium indurate, with bicellular microhairs and simple papillae evenly distributed all over the lemma and palea. Molecular phylogenetic studies, analyzing plastid ndhF and rpoA sequences, confirmed that these morphological characters are differential. The phylogenetic position and taxonomic features of the new genus are established and compared with Panicum s.str. and other taxa of the Sacciolepis–Trichanthecium clade. Full synonymies and descriptions, a distribution map, illustrations of both species, and a key are provided. Two new combinations are proposed. In addition, four African ungrouped species of Panicum s.l. were, for the first time, included in the phylogenetic analysis to analyze their relationship with the new genus and its positions in the Sacciolepis–Trichanthecium clade.